Hubungan Pengetahuan tentang Covid-19 dengan Pemanfaatan Ramuan Tradisional “Empon-Empon” dalam Mencegah Kejadian Covid-19 - Nuriyah Yuliana (Universitas Malahayati Lampung, 2025)
ABSTRACT The condition of Indonesia was shocked by the emergence of the Coronavirus; Indonesia has been in the circle of the coronavirus for ± 12 months. Handling and prevention efforts by the community by maintaining a healthy body can be done through the consumption of traditional herbal medicine to maintain the body's resistance. Some empon-empon plants such as ginger, kaempferia galanga, curcuma zanthorrhiza, turmeric is part of traditional herbal medicine that can be used to maintain endurance and relieve symptoms of illness that lead to some symptoms of the corona. The aim of this study was to determine the relationship between knowledge about COVID-19 and the use of the traditional herb